Analysis of Work Stress, Burnouts, Emotional Intelligence of Organizational Commitments and Nurse Performance of Hermina Hospital Tangkubanprahu Malang - Yuliani Ningsih; Yuly Periostiawati; Nurdina Nurdina (Journal for Quality in Public Health, 2021)
In hospital services, nurses are most vulnerable to stress because they are related to mental safety. Nurse performance is the main factor in determining the success of hospital services.This research design uses explanatory, namely explaining the direct and indirect effects between variables. Research population 135 nurses with precision = 5%, sample (n) of 101. Sampling technique using Probability Sampling, independent variables: Job Stress, Burnout and Emoisonal Intelligence. dependent variable: Organizational Commitment and Nurse Performance. The result of testing the total effect is greater than the direct effect, so the accepted hypothesis shows that the variable organizational commitment can mediate the work stress variable on nurses' performance with a total of = -0.386, the organizational commitment variable can mediate the work fatigue variable on the nurse's performance dg total = -0.280, the commitment variable organizational intelligence can mediate the emotional intelligence variable on the performance of the woman with a total = 0.395.The career success paradigm from Intelligence Quotient (IQ) to Emotional Quotient (EQ) proves that emotional intelligence makes a greater contribution to success and achievement in the workplace compared to intellectual intelligence.